The Influence Of Human Resources Information System Ismarthc And Digital Culture On Employee Performance Of PT Telkom Indonesia Tbk Area Bumi Serpong Damai City Of Tanggerang - Mochamad Rizki Listiana; Taufiq Amir (Jurnal Scientia, 2024)
This research aims to analyze the influence of the Ismarthc Human Resources Information System and Digital Culture on the Performance of PT Telkom Indonesia Tbk Employees in the BUMI SERPONG DAMAI CITY TANGERANG Area. The sample in this research was 55 employees of PT Telkom Indonesia Tbk. The analytical method used is multiple linear regression with data analysis techniques using the SPSS 26 software application. The results of the research conclude that partially the Human Resources Information System has an effect on employee performance, because the sig value is 0.009 < 0.05, and t count is 2,694 > t table 2,007. Digital culture influences employee performance because the sig value is 0.001 < 0.05, and t count is 2.694 > t table 2.007 and the significance value of the F test is 0.00 < 0.05 shows that there is a simultaneous influence between the Human Resources Information System and digital culture on employee performance. The coefficient of determination (R Square) is 0.502, which means that the magnitude of the influence of the Human Resources Information System and digital culture on employee performance is 50.20% and 49.80% influenced by other factors.